MEMBUMIKAN KEISLAMAN DENGAN GERAKAN CINTA AL-QUR'AN - Ummi Ulfariyani Kadir; Sahlan Sidjara; Nurdin Arsyad; Tarisha Nur Asyifa; Nurfadila (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
The ability to read Qur’an is a fundamental skill that should be possessed by every Muslim. Certainly, the ability of each individual some are very fluent, while others may not be able to read Qur’an at all. Learning to read Qur’an should ideally begin at a young age so that children can have a foundation for the future. The differences in abilities can be attributed to various factors, such as the lack of attention from parents to include their children in learning at the Al-Qur’an Eduaction Park (TPA). To address this, KKNT team has initiated the Gerakan Cinta Al-Qur’an (GENTA) program with the aim of enhancing the reading abilites of children for read Qur’an. In addition, children are directed to memorize daily prayers. In order to increase religious knowledge in the community, the GENTA program also provides religious gatherings for the public. The results of these activities show that through the Gerakan Cinta Al-Qur’an program, Islamic culture in the Takkalasi has been strengthened. This can be seen through the increased enthusiasm an motivation of children to enhance their religious knowledge and strengthen interpersonal relationships.